1974
DOI: 10.1002/1097-0142(197407)34:1<184::aid-cncr2820340128>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The carcinoembryonic antigen assay in bronchogenic carcinoma

Abstract: Pretreatment levels of plasma carcinoembryonic antigen (CEA) were determined for a series of patients with bronchogenic carcinoma and for a series of patients with benign pulmonary disease. These data were analyzed to determine the diagnostic and prognostic value of the CEA radioimmunoassay in bronchogenic carcinoma. CEA plasma values in patients with benign pulmonary disease indicate that the level of discrimination between positive and negative tests for bronchogenic carcinoma should be at least 5.0 ng/ml. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(4 citation statements)
references
References 12 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The LUNX gene was mapped to a peri‐centromeric region of chromosome 20, where chromosomal aberrations have been reported in a variety of cancers, such as breast cancer, leukemia, pancreatic cancer and colon cancer 19–22. Furthermore, semi‐quantitative RT‐PCR showed that LUNX expression was more enhanced in most tumors compared with normal background lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The LUNX gene was mapped to a peri‐centromeric region of chromosome 20, where chromosomal aberrations have been reported in a variety of cancers, such as breast cancer, leukemia, pancreatic cancer and colon cancer 19–22. Furthermore, semi‐quantitative RT‐PCR showed that LUNX expression was more enhanced in most tumors compared with normal background lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…If it is intended to use the marker as a screening or diagnostic test, then it must be present in virtually 100% of cases. In this context, Concannon et al (1974) concluded that CEA is of no value in bronchial carcinoma. Similarly, if the marker is to be applied as a test for disseminated disease, and thus exclude patients who are unsuitable for surgery, it must correlate very closely with the presence of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen6 in 1970 described the use of zirconylphosphate gel, the method that we have used for radioimmunoassay of CEA. 4 We believe it is now possible to give some appraisal of the value of CEA in the assessment of the lung cancer patient. In this investigation we are looking to answer, in part, the following questions: 1) Based on data from various control population groups, what concentration of CEA should be regarded as normal?…”
Section: E Increasing Incidence Of Lung Cancermentioning
confidence: 99%